2017
DOI: 10.19045/bspab.2017.600115
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of plant extract and zinc nanoparticles obtained from Syzigium aromaticum L.

Abstract: Nanotechnology deals with the use of nanoparticles in various remarkable fields of present time with vast medicinal, agricultural and industrial applications. Biological approaches using microorganisms and plants or plant extracts for metal nanoparticles, have been suggested as valuable alternatives to chemical methods. In present study Syzigium aromaticum L. extracts in water and ethanol were used for the green synthesis of zinc oxide nanoparticles. After being treated with zinc sulphate solution, the color o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Both S. aureus and S. pneumoniae showed MIC values of 76-100 mg/mL. Additionally, the biosynthesis of ZnO-NPs using S. aromaticum extracts in water and ethanol resulted in the inhibition of K. pneumonia, P. aeruginosa, and E. coli [95]. The study also demonstrated the formation of an inhibition zone against B. subtills, S. aureus, K. pneumonia, and E. coli at a concentration of 100 μg/mL of ZnO-NPs synthesized using Brassica oleracea var.…”
Section: Antibacterial Action Of Zno-npsmentioning
confidence: 99%
“…Both S. aureus and S. pneumoniae showed MIC values of 76-100 mg/mL. Additionally, the biosynthesis of ZnO-NPs using S. aromaticum extracts in water and ethanol resulted in the inhibition of K. pneumonia, P. aeruginosa, and E. coli [95]. The study also demonstrated the formation of an inhibition zone against B. subtills, S. aureus, K. pneumonia, and E. coli at a concentration of 100 μg/mL of ZnO-NPs synthesized using Brassica oleracea var.…”
Section: Antibacterial Action Of Zno-npsmentioning
confidence: 99%
“…Different volumes of seeds hot aqueous extract and ZnSO4 solution were used in manufacture of ZnNPs by adding (45, 25 and 5) mL of 1*10 -3 M ZnSO4 with (5, 25 and 45) mL of seeds hot aqueous extract respectively (Ahmed et al, 2016 andJavad et al, 2017).…”
Section: Evaluate the Use Of Different Volumes From P Crispum Seeds H...mentioning
confidence: 99%